2005
DOI: 10.1212/01.wnl.0000191154.78131.f6
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Parkinson disease

Abstract: While non-demented patients with Parkinson disease had a moderate cholinergic dysfunction, subjects with Parkinson disease associated dementia (PDD) presented with a severe cholinergic deficit in various cortical regions. The finding of a closely associated striatal FDOPA and cortical MP4A binding reduction suggests a common disease process leading to a complex transmitter deficiency syndrome in PDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
239
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(262 citation statements)
references
References 27 publications
18
239
2
3
Order By: Relevance
“…In vivo imaging studies have also shown that the presence of dementia in PD is associated with more severe and widespread cholinergic denervation compared with PD without dementia (Bohnen et al, 2003;Hilker et al, 2005;Kuhl et al, 1996;Shinotoh et al, 1999). These imaging results are consistent with post-mortem evidence that basal forebrain cholinergic system degeneration appears early in PD and worsens in parallel with the appearance of dementia (Ruberg et al, 1986).…”
Section: Heterogeneity Of Cholinergic Denervation In Pd and Clinical supporting
confidence: 74%
See 1 more Smart Citation
“…In vivo imaging studies have also shown that the presence of dementia in PD is associated with more severe and widespread cholinergic denervation compared with PD without dementia (Bohnen et al, 2003;Hilker et al, 2005;Kuhl et al, 1996;Shinotoh et al, 1999). These imaging results are consistent with post-mortem evidence that basal forebrain cholinergic system degeneration appears early in PD and worsens in parallel with the appearance of dementia (Ruberg et al, 1986).…”
Section: Heterogeneity Of Cholinergic Denervation In Pd and Clinical supporting
confidence: 74%
“…In contrast to severe striatal dopaminergic terminal losses, exceeding 50% to 80% in PD subjects with clinically manifest motor symptoms Guttman et al, 1997), in vivo acetylcholinesterase studies show cholinergic projection losses in the magnitude of 5% to 25% in PD subjects without or with dementia (Bohnen et al, 2003;Hilker et al, 2005;Shimada et al, 2009;Shinotoh et al, 1999). The more limited and variable cholinergic losses suggest the presence of overlap in cholinergic projection system integrity between PD and control groups.…”
Section: Introductionmentioning
confidence: 95%
“…In this study, we confirmed a similar loss of DA transporter and TH in the striatum of both PD groups. According to published reports [21,40], there is no difference in vivo in the rate or extent of dopaminergic degeneration between patients with PD and PD with dementia. Our post mortem results generally support that conclusion.…”
Section: Upregulation Of Arrestin and Grk Expression In Parkinson's Dmentioning
confidence: 99%
“…[ 18 F]dopa PET has shown that early-stage PD patients displayed a rapid progression of dopaminergic denervation in the putamen with a posterior-to-anterior gradient and a side-to-side asymmetry between the less and more affected striatal structures (Hilker, Schweitzer, et al, 2005;Hilker, Thomas, et al, 2005;Nandhagopal et al, 2009). In advanced stages, dopaminergic degeneration becomes slower, and although the gradient is maintained, the degree of asymmetry diminishes (Hilker, Schweitzer, et al, 2005;Hilker, Thomas, et al, 2005;Nandhagopal et al, 2009). The mean annual decline in [ 18 F]dopa uptake ranges from 8% to 12% in the putamen and from 4% to 6% in the caudate and it is considerably more than the decline typical of aging (Nurmi et al, 2001;Pavese, Rivero-Bosch, Lewis, Whone, & Brooks, 2011).…”
Section: Dopaminergic Systemmentioning
confidence: 99%
“…The mean annual decline in [ 18 F]dopa uptake ranges from 8% to 12% in the putamen and from 4% to 6% in the caudate and it is considerably more than the decline typical of aging (Nurmi et al, 2001;Pavese, Rivero-Bosch, Lewis, Whone, & Brooks, 2011). Moreover, presynaptic dopaminergic PET imaging has been used to estimate the duration of preclinical PD and it has shown 30%-55% loss of putamen dopaminergic function at the time of symptom onset (de la Fuente-Fernández et al, 2011;Hilker, Schweitzer, et al, 2005;Hilker, Thomas, et al, 2005;Lee, 2000). [ 11 C]DTBZ PET imaging estimated a preclinical state lasting up to 17 years, and [ 11 C]MP PET has shown a period of up to 13 years in patients with PD who were diagnosed at just over 50 years of age.…”
Section: Dopaminergic Systemmentioning
confidence: 99%